Ansiedad matemática hacia la evaluación sumativa. Un análisis entre estudiantes de tercero y octavo grado en un colegio privado de Soacha. (2023)
The present research work entitled “Mathematical anxiety towards summative evaluation. A comparison between third and eighth grade students in a private school in Soacha” is based on a problem observed in primary school (third) and high school (eighth) students when taking an evaluative test in mathematics class.